Faktor-Faktor yang Mempengaruhi Penghindaran Pajak pada Perusahaan Energi, Bahan Baku dan Industri yang Terdaftar di Bursa Efek Indonesia - Maharani, Nabila Intan; Nuswandari, Cahyani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The researcher's objective is to analyze debt, company size, and sales growth on tax avoidance. The population of this study is energy, raw materials, and industrial subsector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. This study uses purposive sampling technique for sampling so that there are 89 companies that meet the data determination requirements. Company data that was sampled as many as 89 is panel data. So the number of samples during 2020-2022 is 3x89 = 267 companies. The result is that the leverage variable has a significant negative effect on tax avoidance, the company size variable has no effect on tax avoidance, and the sales growth variable has a significant negative effect on tax avoidance.